The suffering of a victim of child sexual abuse - Norhidayah Daud; Faizah Abd Ghani (Journal of Counseling and Educational Technology, 2020)
Stressful early life experiences may cause traumatic experience across the lifespan. The aim of this study was to explore a CSA female victim’s lived-experience. Interviews were conducted with this 13-year-old girl, N, using a case study approach. N was still a young child (seven years old) when her uncle started to rape her, and when she was 10 years old, her father raped her. Since her childhood, she has experienced complex and widespread consequences such as vaginal and abdominal pain, shivering, sleeping problems, digestive problems, back problems, emotional and cognitive problems such as she was thinking to commit suicide, scared that her uncle and father will come to her, dissociation, study problems and isolation. N’s situation, might reflect similar problems in other female CSA victims.